2003
DOI: 10.1046/j.1365-2842.2003.01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maximum bite force and craniofacial morphology of young adults in Indonesia

Abstract: The present study was conducted to evaluate the relationship between maximum bite force and craniofacial morphology. Sixty-four Indonesian female dental students aged 19-27 years with normal occlusion served as the subjects. The Dental Prescale System was used to measure the maximum bite force using a pressure sensitive sheets while craniofacial morphology measurements were determined from conventional lateral radiograms. The antero-posterior and right-left position of the occlusal load centre (the OLC) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
2
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 36 publications
(77 reference statements)
7
52
2
7
Order By: Relevance
“…In addition, mastication also has a substantial effect on craniofacial morphology. Previous studies pointed to a correlation between the maximum bite force (MBF) and facial morphology (Abu Alhaija, Al Zo'ubi, Al Rousan, & Hammad, 2010; Braun et al, 1995; Proffit, Fields, & Nixon, 1983; Ringqvist, 1973; Sondang et al, 2003; Szymańska & Sidorowicz, in press). The mean bite force was twice as great in the normal as in long face subjects (Proffit et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mastication also has a substantial effect on craniofacial morphology. Previous studies pointed to a correlation between the maximum bite force (MBF) and facial morphology (Abu Alhaija, Al Zo'ubi, Al Rousan, & Hammad, 2010; Braun et al, 1995; Proffit, Fields, & Nixon, 1983; Ringqvist, 1973; Sondang et al, 2003; Szymańska & Sidorowicz, in press). The mean bite force was twice as great in the normal as in long face subjects (Proffit et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The mean bite force was twice as great in the normal as in long face subjects (Proffit et al, 1983). Sondang et al (2003) reported that a larger bite force implies a greater mandibular plane angle and smaller gonial angle, suggesting that long face subjects exert a lower level of bite force. Thus, subjects with dolicho facial morphology are likely to have inferior masticatory efficiency (Gomes, Custodio, Jufer, Del Bel, & Garcia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A pressure-sensitive film (Dental Prescale; Fuji Photo Film Co., Tokyo) is one such device 10,20) which has been used for occlusal force measurement in a number of studies 5,6,8,11,13,15,16,18) . It is designed to quantify occlusal pressure from occlusal contact marked on a thin horseshoe-shaped strip of film.…”
Section: Introductionmentioning
confidence: 99%
“…This system is now being used in various fields of dental research, particularly by Japanese researchers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33] . These studies have suggested that this system might help evaluating masticatory function and could be applicable to general dental clinical work.…”
Section: Introductionmentioning
confidence: 99%